Forecasting Wage Inequality - Ruiz-Tagle, Jaime (Estudios de Economía, 2016)
Wage inequality in Chile has remained high for decades and it is currently at thecenter of the political agenda. Increasing education of workers is expected tocontribute to reduce wage inequality. Based on historical trends of age, education,and returns to education, this paper attempts to forecast wage inequality.Despite an increase in average earnings due to higher levels of education ofworkers, high levels of wage inequality within age groups and within educationgroups produce that forecasted wage inequality remains high for the next 10-year period. The structure of the Chilean labor market appears to imply thatthere is a high level of underlying wage inequality. Nevertheless, the good newsare that the labor market structure seems to prevent further deteriorations ofwage inequality.